2004
DOI: 10.1007/s00011-003-1216-2
|View full text |Cite
|
Sign up to set email alerts
|

GM-CSF counteracts hemorrhage-induced suppression of cytokine-producing capacity

Abstract: Hemorrhagic shock caused a depression of the TNFalphaa response to LPS which was partly counteracted by treatment with GM-CSF. Therefore, GM-CSF represents a promising approach to normalise trauma- and shock-induced immune dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2004
2004
2007
2007

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…In view of this, it appears that rats might also have different plasma IL-10 kinetics than mice, which explains the difference between our present findings and those of the previous study. The present results also showed that the production capacity of proinflammatory cytokines, IL-6 and TNF-␣, was increased by Kupffer cells, but their production by splenic macrophages, alveolar macrophages, and PBMC was decreased following trauma-hemorrhage, consistent with the previous findings (4,14,23,38). Moreover, the production capacity of the antiinflammatory cytokine IL-10 by Kupffer cells, splenic macrophages, alveolar macrophages, and PBMC was increased.…”
Section: Discussionsupporting
confidence: 92%
“…In view of this, it appears that rats might also have different plasma IL-10 kinetics than mice, which explains the difference between our present findings and those of the previous study. The present results also showed that the production capacity of proinflammatory cytokines, IL-6 and TNF-␣, was increased by Kupffer cells, but their production by splenic macrophages, alveolar macrophages, and PBMC was decreased following trauma-hemorrhage, consistent with the previous findings (4,14,23,38). Moreover, the production capacity of the antiinflammatory cytokine IL-10 by Kupffer cells, splenic macrophages, alveolar macrophages, and PBMC was increased.…”
Section: Discussionsupporting
confidence: 92%
“…Ex vivo exposure to GM-CSF has restored function in monocytes harvested from humans with septic shock (36) or from immunosuppressed liver transplant recipients (37). In a rat model of hemorrhagic shock, GM-CSF treatment in vivo has corrected tissue macrophage dysfunction (17). Our data are of particular interest because we have shown both that reduced local expression of GM-CSF is likely to account for AM dysfunction following sublethal hyperoxia and that treatment with GM-CSF largely corrects this defect.…”
Section: Discussionmentioning
confidence: 65%
“…In sepsis-associated immune dysfunction the administration of GM-CSF was able to counteract the reduced HLA-DR expression on monocytes as well as the reduced TNF-alpha producing capacity of whole blood cultures (Nierhaus et al, 2003). Concerning haemorrhagic shock, it has been demonstrated that GM-CSF given immediately after reperfusion could restore the diminished TNF-alpha response of spleen and peritoneal cells (Husain et al, 2004). When GM-CSF is given in vivo the restoration of the cytokine response may be explained by the generation of new macrophage populations from the bone marrow, which of course is activated by the haematopoietic growth factor GM-CSF.…”
Section: Shammentioning
confidence: 96%
“…GM-CSF is also reported to restore the reduced TNFalpha production of splenic and peritoneal macrophages after haemorrhagic shock in rats (Husain et al, 2004).…”
Section: Introductionmentioning
confidence: 97%